Organizational and individual barriers and facilitators to the integration of pediatric palliative care for children: A grounded theory study. (September 2021) - Laronne, Anat; Granek, Leeat; Wiener, Lori; Feder-Bubis, Paula; Golan, Hana
Background: Pediatric palliative care has established benefits for children with cancer and their families. Overcoming organizational and healthcare provider barriers have been demonstrated as central for the provision of palliative care in pediatric oncology. A deeper understanding is needed of the influence of these barriers and the interactions between them, specifically in primary palliative care in hospital settings. Aim: To identify the organizational and healthcare provider barriers to the provision of primary pediatric palliative care. Design: This study utilized the grounded theory method. Semi-structured interviews were conducted and analyzed line by line, using NVivo software. Setting/participants: Forty-six pediatric oncologists, nurses, psychosocial team members, and other healthcare providers from six academic hospital centers participated in the research. Results: Organizational and healthcare provider factors were identified, each of which acted as both a barrier and facilitator to the provision of pediatric palliative care. Organizational barriers included lack of resources and management. Facilitators included external resources, resource management, and a palliative care center within the hospital. Individual barriers included attitudes toward palliative care among pediatric oncologists, pediatric oncologists' personalities, and the emotional burden of providing palliative care. Facilitators include dedication and commitment, initiative, and sense of meaning. Provider facilitators for palliative care had a buffering effect on organizational barriers. Conclusion: Organizational and healthcare provider factors influence the quality and quantity of palliative care given to children and their families. This finding has implications on interventions structured to promote primary palliative care for children, especially in healthcare systems and situations where resources are limited.